Fuzzy super irresolute functions - S. E. Abbas (International Journal of Mathematics and Mathematical Sciences)
The concept of fuzzy super irresolute function was considered and studied by ostak's (1985). A comparison between this type and other existing ones is established. Several characterizations, properties, and their effect on some fuzzy topological spaces are studied. Also, a new class of fuzzy topological spaces under the terminology fuzzy S∗-closed spaces is introduced and investigated.